ANALISIS TINGKAT RISIKO KELUHAN SISTEM MUSKULOSKELETAL DENGAN METODE NORDIC BODY MAP DAN STRES KERJA KAYAWAN BAGIAN PRODUKSI PT TIRTA SARI SURYA INDRAGIRI HULU - Kode Wiranda Welya; Daulay Nauli Iwan; Paramitha Anggia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
Complaints of Musculoskeletal Disorders (MSDs) and Work Stress are one of the problems that frequently occur in employees that can interfere with work productivity with this phenomenon, this study aims to describe the level of risk of musculoskeletal system complaints and an overview of the level of work-related stress in employees in the production department. PT Tirta Sari Surya Indragiri Hulu. The population in this study included all employees of the production division in 2020 who work at PT Tirta Sari Surya Indragiri Hulu, which has 374 employees, the sample calculation is carried out employing the Slovin technique on as many as 80 respondents. Data were collected using a standardized and valid questionnaire. The method used to affect the level of complaints of the musculoskeletal system represent the Nordic Body Map method. The method of assessing the level of work stress is the scoring method and the stress research questionnaire from the Health and Safety Executive with 5 Likert scales. The results indicated that from 80 respondents, and it was portrayed that: 1) the level of risk of musculoskeletal system complaints was 30 respondents (37.5%) in the moderate risk category, 46 respondents (60%) in the high-risk category and 2 respondents (2.5%) in the very high-risk category. The highest risk level for musculoskeletal system complaints is in the high risk category, so immediate corrective action is needed from the company and employees. The results of the Nodic Body Map questionnaire show the category of complaints of mild pain in the elbows and thighs. The category of complaints is cramp in the neck, shoulders, superior arms, waist, hips, forearms, and wrists. The category of complaints is terribly sick in the back of the body. 2) the level of work stress risk as many as 6 respondents (7.5%) in the moderate stress risk category and 74 respondents (92.5%) in the high stress risk category. The level of work stress is dominated by the high risk category, so immediate corrective action is needed from the company and employees.Keywords: Musculoskeletal System Complaints, Work Stress, Nordic Body Map, Health and Safety Executive